EMOTIONAL INTELLIGENCE & DIGITAL LEADERSHIP: MENGAPA KECERDASAN EMOSIONAL TETAP PENTING DI ERA AI - Wanti Mustika Rini; Winda Oktavia Ramadhina; Ahmad Hasinul Adabi; Mochammad Isa Anshori (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Emotional intelligence (EQ) and digital leadership are critical elements in addressing the challenges of the technological transformation era accelerated by artificial intelligence (AI). This article aims to analyze the role of EQ in enhancing digital leadership effectiveness, identifying challenges faced by leaders, and providing practical recommendations for organizations. The research employs a systematic literature review method from reputable journals such as Scopus and Sinta, focusing on publications from the past five years. The findings reveal that EQ is vital in building interpersonal relationships, managing stress, and fostering an inclusive work culture even in virtual settings. Leaders with high EQ can understand employees' emotional needs, provide appropriate support, and create innovative and collaborative work environments. However, key challenges such as limited face-to-face interactions, reliance on technology, and pressure to achieve high performance require specific strategies to integrate EQ into digital leadership practices. This article concludes that EQ is not merely an additional skill but a fundamental element that can enhance organizational performance and employee well-being in the digital era. By effectively applying EQ principles, leaders can establish a healthy, productive work culture that adapts to technological changes.